The complete guide to blender graphics : computer modeling & animation - Blain, John M., 1942- (CRC Press, Taylor & Francis Group, 2021)
"Blender is a free Open Source 3D Computer Modeling and Animation Suite incorporating - Character Rigging, Particles, Real World Physics Simulation, Sculpting, Video Editing with Motion Tracking and 2D Animation within the 3D Environment. Blender is FREE do download and use by anyone for anything. The Complete Guide to Blender Graphics: Computer Modeling and Animation 6th Edition is a unified manual describing the operation of the program with reference to the Graphical User Interface for Blender Version 2.82a"- Resumé vydavatele
Keywords: počítačová animace; počítačová grafika; trojrozměrná grafika; počítačové modelování; Blender (software); computer animation; computer graphics; three-dimensional graphics; computer modeling; příručky; handbooks and manuals